THE EFFECTIVE TEMPERATURES OF K-GIANTS - Mishenina, T. V.; Korsak, V. V. (Одеські астрономічні публікації, 2017)
The spectral classification of stars based on the ratios of the line depth, which are sensible to the temperature changes. Such calibrations were used for various stars (Gray, 1994; Kovtyukh et at., 1998). From the high- resolution spectra of K-giants, we selected 15 pairs of atomic lines and we derived 15 analytical relations for the determination of effective temperature Teff . Our calibrations were constructed for 5000 K <Teff <4000 K and for [Fe/H] from 0 to -1 dex. The abundance dependence is taken from the synthetic spectral calculations by the Kurucz's (1993) models. We determine Teff for Arcturus on the high resolution high dispersion spectra obtained at different times.